Introduction to Financial Literacy in the Muara Penimbung Community - Hendra Prasetyo; Sri Maryati; Maiza Fikri; Yuli Alam; Asiawati (Indonesian Journal of Community Engagement, 2026)
Financial literacy is an individual’s ability to understand and effectively manage financial resources in order to improve household economic well-being. Low levels of financial literacy remain a major challenge in rural communities, particularly due to limited access to formal financial information and education. This community service activity aims to introduce and enhance basic financial literacy among the Muara Penimbung community through an educational and participatory approach. The implementation methods include counseling sessions, interactive discussions, and simulations of household financial recording and planning. Evaluation was conducted through participatory observation and question-and-answer sessions to identify changes in community understanding before and after the activity. The results indicate an improvement in community understanding of household financial management, the distinction between needs and wants, and the importance of family financial planning. Overall, this activity makes a positive contribution to promoting more prudent and sustainable financial behavior at the village level.